Beyond Inclusion and Exclusion: Community Gardens as Spaces of Responsibility. Issue 3 (4th May 2017) - Neo, Harvey; Chua, C. Y.
Abstract : Geographers have a sustained interest in urban community gardens because such spaces provide a meaningful lens to interrogate the complexities of living at the intersection of nature–society relationships. Most community gardens strive to perform the dual functions of reconnecting urban residents with nature and strengthening the community. More recently, in the context of neoliberal urban restructuring, community gardens have also been viewed as platforms for the mobilization of inclusive sociopolitical arrangements to counteract the ill effects of urban problems. Common to this literature is the implicit assumption that a good community garden must necessarily be inclusive or that, conversely, community gardens that are exclusionary are bad. We argue that framing community gardens as spaces of responsibility is another way to reengage with the epistemology of community gardens. Instead of only asking how, and to what extent, community gardens are inclusionary or exclusionary, we can augment our understanding of the realities of managing a garden by asking what responsibilities are associated with any given community garden. Among other things, the answer to this question requires one to trace the responsibilization process of gardeners. Through the case study of Singapore, we argue that responsibilization invariably engenders practices of inclusion and exclusion in community gardens. Framed thusly, we first move away from the reductive view that apparent exclusionary practices in a community garden render that garden to be normatively undesirable. Second, we can appreciate why many community gardens—even seemingly inclusive ones—have shades of exclusions embedded in them.